Pelatihan Design dengan Aplikasi Canva sebagai Sarana Promosi Produk di Desa Bulupayung, kecamatan Kesugihan, kabupaten Cilacap - Rifani, Endang; Roihanah, Ana; S, Solikhun; P, Purwati; Arifin, Zaenal; Kustiansyah, Nakula Bagus; Huda, M. Hanif Nur; M, Masrukhin; Milenia, Laela Yusriyah; Prayuda, M. Amril; Brilianto, Abra; Fauzy, Achmad; Santosa, Ade; Syafei, Muhammad (Yayasan Daarul Huda Kruengmane, 2025)
This service aims to increase the creativity of MSME actors in creating more modern logos using the Canva application as a means of product promotion because a logo is a very important thing in starting a business. Logo design can also influence the formation of a product image. With a logo, it can reflect the identity of the product itself so that it is better known to many people. The method used in the training is the demonstration and practice method. The results of this activity are that the use of the Canva Application in creating logos is quite simple and easy to understand by changing fonts, changing color combinations, and adding text and product images using the main features, namely drag and drop, then continued with the implementation of practices carried out by MSME actors and can produce logos according to the objectives, namely more creative and modern logos.